An energy saving clustering algorithm based on artificial bee colony in ultra dense network - Zhou, Pengguang; Huang, Junwei; Zhang, Renchi; Xu, Hao (Dianxin Kexue, 2017)
In ultra dense network(UDN), the dense deployment of low power base station(BS) will increase the system's energy consumption and cause the waste of the scarce spectrum resources. Aiming to explore the feasible method of energy saving system and interference coordination, BS sleeping-waking-active mechanism in UDN was proposed, which would reduce the opening time of the sleeping BS. Also an adjusted artificial bee colony algorithm was proposed which used the least colors to dye the BS in topology, then power allocation of active BS in different cluster was optimized. Simulations show that the sleeping-waking-active mechanism can improve the energy efficiency of the system, and the clustering algorithm can promote the spectrum efficiency and throughput.